2017
DOI: 10.11118/actaun201765010219
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Briquettes Produced from Energy Plants

Abstract: The study deals with the use of energy crops for the production of thermal energy in the form of briquettes and devising appropriate parameters for their production. Briquettes were produced from seven kinds of energy crops, Salix viminalis, Miscanthus sinensis, Rosa multiflora, Polygonum sachalinensis, Helianthus tuberosus, Sida hermaphrodita and Spartina pectinata, specifically. In the production of briquettes, moisture is the most important properties of material to be pressed, which ranges from 8 to 15 % a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…They suggested replacing artificial drying with storage, allowing S. hermaphrodita stems to dry naturally for six months. Urbanovičová et al [126] produced S. hermaphrodita briquettes using a hydraulic press, reporting a calorific value of 15 MJ kg −1 . They reported that the briquettes had a similar density, durability, moisture content, and calorific values as briquettes produced from other crops.…”
Section: Growing Sida Hermaphrodita and Silphium Perfoliatum As Solidmentioning
confidence: 99%
“…They suggested replacing artificial drying with storage, allowing S. hermaphrodita stems to dry naturally for six months. Urbanovičová et al [126] produced S. hermaphrodita briquettes using a hydraulic press, reporting a calorific value of 15 MJ kg −1 . They reported that the briquettes had a similar density, durability, moisture content, and calorific values as briquettes produced from other crops.…”
Section: Growing Sida Hermaphrodita and Silphium Perfoliatum As Solidmentioning
confidence: 99%
“…Common densification systems that are typically used in the biomass industry are pellet mill and briquette press (Tumuluru et al, 2011). A pellet mill typically produces a densified product with a bulk density of 650 to 750 kg/m 3 , whereas a briquette press produces a densified product with a bulk density of 350 to 450 kg/m 3 and unit densities of 600-850 kg/m 3 (Tumuluru et al, 2011;Urbanovičová et al, 2017;Mani et al, 2006;Ndindeng et al, 2015). The quality of the densified product produced using pellet mill and briquette press depends on process conditions such as length-to-diameter ratio or compression ratio of the pellet die, die diameter, and biomass properties (particle size of the grind, biomass moisture content, and biomass composition).…”
Section: Introductionmentioning
confidence: 99%
“…Kandungan abu yang tinggi dapat menurunkan nilai kalor briket sehingga kualitas briket semakin rendah [4]. Semakin besar nilai kalorinya maka semakin banyak energi termal yang dihasilkan oleh pembakarannya [5]. Tempurung kawista sangat berpotensi sebagai karbon aktif [3].…”
Section: Pendahuluanunclassified
“…Crucible dipindahkan dari tanur, didinginkan dalam desikator, dan ditimbang segera. Kadar abu (%) dihitung dengan persamaan (5).…”
Section: Pengukuran Kadar Abuunclassified